STRATEGIC FLEXIBILITY OF ZVO IN THE FORMATION OF COMPETITIVE GOALS IN THE CONDITIONS OF CHANGES - VERBOVSKA, Lesya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the issue of strategic flexibility of higher education institutions in modern conditions. The relevance of the study of the strategic flexibility of higher education institutions in the formation of competitive goals in conditions of change is determined by modern trends in the competitive advantages of higher education institutions; adaptation of flexible development strategies; partnership cooperation with European universities; increasing the competitiveness of the teaching staff; diversification of new areas of scientific activity and new opportunities for development. In the process of writing a scientific article, various general scientific research methods are used. An analysis of the development strategies of four institutions of higher education was carried out, namely, Ivano-Frankivsk National Technical University of Oil and Gas (Ivano-Frankivsk, Ukraine), Lviv Polytechnic (Lviv, Ukraine), Mining and Metallurgical Academy named after S. Staszyca (Krakow, Poland), Poznań Polytechnic (Poznań, Poland). The conducted analysis showed that the most important element is the goals and objectives, and their components are determined primarily not by strategic planning due to the improvement of the quality of education and the positioning of higher education institutions as a competitive market of educational services, it’s the adaptation to market conditions, the formation of a competitive specialist capable of working at the international level, the search and attraction of consumers, analysis of activities of educational institutions, analysis of provision of educational services to consumers, diversification of educational activities in order to enter the European market of educational services.The practical value of the research lies in the thorough analysis of development strategies for the implementation of flexible management of institutions of higher education in a changing, flexible and competitive environment. Strategic flexibility will allow to form a new environment of "VUKA" and "BANI", because in difficult conditions, competitiveness of the university is quite important.
Keywords: institution of higher education; strategic flexibility; competitive goals; changes; leadership